Revising Fiscal Policy and Growth in Saudi Arabia - Mann, Janelle; Sephton, Peter (Journal of Reviews on Global Economics, 2015)
This article empirically investigates how private investment and different categories of public expenditure (defense, education, health care, and housing) impact real non-oil GDP in Saudi Arabia. The econometric analysis couples unit root, stationarity, and cointegration analysis with vector error correction models. Impulse response functions are applied to examine the impacts of different shocks to the system. We find that public expenditures on health care and defense have decreased real non-oil GDP while public expenditure on education and housing have very little impact. Interestingly, public expenditures on health crowds-out private investment.